PERENCANAAN SISTEM REKAM MEDIS BERDASARKAN INPUT DAN PROSES DI TEMPAT PENDAFTARAN PASIEN RAWAT JALAN PUSKESMAS BANGUNTAPAN II KABUPATEN BANTUL TAHUN 2011 - Khasanah, Yuli Uswatun; Rosyidah, . (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background : Paradigm of a healthy life can be the foundation for better understanding the complexities of public health issues. Four main factors that influence health status of individuals/communities, among other behavioral factors, environmental, health and genetic services. Health factors play a role in this concept is the third largest. Health care institutions are also required to improve quality in providing outstanding service, such as by improving the quality of medical record keeping activities.High and low quality of health services can be seen from the data whether or not complete treatment are listed in the medical record. Medical records are very important in carrying out the quality of medical care. A medical record has seven competencies, one of which is a medical records management unit. Place of registration of patients in Puskesmas Banguntapan II regency there are still many problems. So, it needs planning system in order to improve the quality of health services. The research objective is planning a medical record system based on inputs and processes at patient registration. Methode : This was descriptive research using qualitative method. Data collection techniques using observation, interviews and documentation tools while using field notes, check lists, interview guides, tape recorder, and stationery. Analysis of studies using data reduction, data presentation, and drawing conclusions. Result : The results showed that there was many problems in the review of resource inputs (man, money, materials, methods, mechine, and the market) so that it can identify the problem. Based on the identification of the problem it will get priority problems and causes of the problems that arise alternate problem solving. Under an agreement resolving the jury was selected from several alternative settlement of existing problems. The results of selected problem-solving that will be the planning system. Conclusion: there was many problems in the review of resource inputs (man, money, materials, methods, mechine, and the market) and the planning system in particular parts of the registration of medical records of patients can be prepared based on the analysis of the situation. Keywords : Planing, records management unit, out patient